2015
DOI: 10.1097/inf.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Determinants of Immunity to Diphtheria for Children Living in Two Districts of Contrasting Incidence During an Outbreak in East Java, Indonesia

Abstract: Significant variation exists in vaccine coverage and seroprevalence of immunity to diphtheria in East Java. Immunity in high incidence districts is likely because of natural immunity acquired through exposure to toxigenic C. diphtheriae. Booster vaccines are essential for achieving protective levels of immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 12 publications
3
41
5
4
Order By: Relevance
“…A seroprevalence study by Hughes et al in Indonesian children concluded that high DTP3 vaccination coverage does not provide long-term immunity when compared with low vaccination coverage (Hughes et al 2015). Earlier research led to speculation that natural variations in dtxR and tox genes may be associated with the bacterial ability to produce a toxin (Perera and Corbel 1990).…”
Section: Discussionmentioning
confidence: 99%
“…A seroprevalence study by Hughes et al in Indonesian children concluded that high DTP3 vaccination coverage does not provide long-term immunity when compared with low vaccination coverage (Hughes et al 2015). Earlier research led to speculation that natural variations in dtxR and tox genes may be associated with the bacterial ability to produce a toxin (Perera and Corbel 1990).…”
Section: Discussionmentioning
confidence: 99%
“…A diphtheria epidemic in the former Soviet Union in the 1990s resulted in N 157.000 cases claiming~5000 lives (Dittmann et al, 2000). Yet, this pathogen is not under control, and the have been multiple outbreaks in different countries since 2000 including Colombia (Landazabal et al, 2001), India (Parande et al, 2014;Saikia et al, 2010), Norway (Rasmussen et al, 2011), Nigeria (Besa et al, 2014), Thailand (Wanlapakorn et al, 2014), and more recently in Brazil (Santos et al, 2015), Laos (Nanthavong et al, 2015) and Indonesia (Hughes et al, 2015).…”
Section: Diphtheriae Is Genetically Diversementioning
confidence: 94%
“…The incidence in East Java Province is the highest in Indonesia. At the same period, Indonesia was in the second rank in the world, after India (Hughes et al, 2015;WHO, 2015). The peak in East Java occured in 2012 with 955 cases where 37 patients deceased.…”
Section: Introductionmentioning
confidence: 99%